Transcriptional blood signatures of sarcoidosis, sarcoid-like reactions and tubercolosis and their diagnostic implications - Tchernev, Georgi; Chokoeva, Anastasiya Atanasova; Tana, Marco; Tana, Claudio (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2016)
N/A